PROSPEK DAN TANTANGAN PERKEMBANGAN REKSADANA SYARIAH DI INDONESIA - Iim Muhayati (LPPM STAI DARUSSALAM LAMPUNG, 2020)
The Islamic economy and finance in Indonesia, which is increasingly developing in a positive direction, is an encouraging matter for the majority of Indonesian people who are Muslim. Conventional economic activities that have been developing have contained elements of speculation and the existence of an interest system that is considered to suffocate the public, including in capital market activities. The development of the capital market in Indonesia currently has a special attraction for investors. However, to be able to invest directly, there are several obstacles faced by investors such as limited knowledge, information and time. One alternative investment instrument that can be a solution to these constraints is Mutual Funds. Islamic mutual funds exist to complement the diversity of existing conventional mutual funds to be an investment choice for investors, not only Muslim investors but investors in general. Islamic mutual funds in Indonesia from 2010-2019 continued to increase both in quality and quantity. However, the development of sharia mutual funds also faces challenges, namely the challenges of applying the sharia principle itself which must be maintained so that sharia mutual funds continue to run in accordance with sharia principles.